Profitability Analysis of The Smoked Fish Agroindustry in Malalanda Village Kulisusu District, North Buton Regency - Mirsat, Mirsat; Rianda, La; Indarsih, Yusna; Surni, Surni (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2023)
This research aims to (a) determine the smoked fish processing process, (b) determine the costs and income of the smoked fish agroindustry and (c) determine the profitability of the smoked fish agroindustry in Malalanda Village, Kulisusu District, North Buton Regency. Determination of the research area was carried out purposively. Analysis is used to determine the relative profits of a business using the Revenue Cost Ratio or R/C. Net Profit Margin is used to measure the agro-industry's ability to generate net profits from sales made by the agro-industry. The results of the research show that the profitability analysis of the smoked fish agro-industry in Malalanda Village, Kulisusu District, North Buton Regency in the smoked fish processing process uses stages, namely selecting raw materials, cleaning and splitting the fish, piercing and clamping the fish, cutting process, washing process and fish smoking process. Based on the Net Profit Margin (NPM) of sample A and sample B businesses from November - April for sample A it is at 29%, 27%, 24%, 30%, 24%, and 29%, and for sample B it is at 38 %, 38%, 38%, 38%, 37%, and 35%, so it can be seen that the smoked fish business can generate good net profits.